Risk of musculoskeletal injuries associated with the use of computers. Case of study (REDEL. Revista Granmense de Desarrollo Local, 2021)
The increase in teleworking under the new normal through the use of computers, with the means available in homes, results in the appearance of musculoskeletal disorders (MSD), with a low perception of the risk to which users are exposed when these jobs they are not properly designed. A review of the methods described in the bibliography to evaluate postural load was carried out and it was concluded that the best method to evaluate the postural load of computer users is the Rapid Office Strain Assessment method, ROSA (Rapid Office Strain Assessment) applied to a job position as a case study. Due to its simplicity, computer users can use the method as a self-assessment.
Keywords: ergonomics; postural load; musculoskeletal disorders; rosa method